Conceptual issues in the use of cassava modelling for improved production in drought environments - Ekanayake, I.J. (1998)
Drought is responsible for large reductions in cassava root yields. On-farm root yields can be improved two- to three-fold and quality of fresh and processed products improved by the adoption of recently improved production technologies. The potential usefulness is high for genetic, morphological, physiological, and agronomic interventions. The use of cassava growth models can be valuable in the decision-making process to improve cassava productivity. The use of a modelling approach to minimise the savannah farmers' risk in cultivating cassava in drought environments is high. However, this approach needs urgent attention to improve on delivery of outputs to cassava growers. Conceptual and logistical issues associated with the use of cassava growth modelling approach to assess the fitness of improved interventions are discussed.